STUDENTS’ MATHEMATICAL REPRESENTATION ABILITY IN SOLVING PISA PROBLEM - Ahbi Mahdianing Rum; Dadang Juandi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
This study aims at describing students’ mathematical representation ability in solving PISA problem. Qualitative research was used in this study. Participants of the research were 28 students of IX A at junior high school 01 North Bengkulu. Data collected through representation ability skill test, questionnaire and interview. Data analysis revealed that students were able to solve PISA problems but still face some difficulties in presenting mathematical representations related to the solutions of PISA problem. Many students are able to solve the PISA questions having been given with the correct calculations and reasonable logic. Unfortunately, they have a low verbal representation ability. It is showed when students face difficulty writing down what is on their minds precisely. Furthermore, very few students solve the problem using symbol representation. In addition, very few students are able to present visual representations correctly. Most of the graphs made by students are still imprecise or totally incorrect.